Rapid reinflation following the 2011–2012 rhyodacite eruption at Cordón Caulle volcano (Southern Andes) imaged by InSAR: Evidence for magma reservoir refill. Issue 18 (27th September 2016) - Delgado, Francisco; Pritchard, Matthew E.; Basualto, Daniel; Lazo, Jonathan; Córdova, Loreto; Lara, Luis E.
Abstract: Cordón Caulle is a large fissural volcano that has erupted rhyodacitic magma of the same composition in its past three historical eruptions in 1921, 1960, and 2011–2012. There was significant ground deformation observed before and during the 2011–2012 eruption—here we use C and X band interferometric synthetic aperture radar (InSAR) time series results to document posteruptive uplift up to 0.8 m between March 2012 and May 2015, with line‐of‐sight rates up to 45 cm/yr that have been largely aseismic, along with subsidence in the 2011–2012 lava flow. The 2012 uplift rate is one of the largest for silicic systems and was likely produced by the intrusion of 0.125 km 3 of magma in the same tectonically controlled plumbing system that has been active during the historical eruptions. Nevertheless, the uplift ended before the reservoir refilled with the erupted volume, maybe due to a change in the pressure gradient produced by the 2011–2012 eruption. Key Points: Extremely high uplift rate after the only rhyodacitic eruption that has been scientifically monitored and observed Inflation is consistent with magma recharge in a long‐lived chamber active during the volcano historical eruptions Despite its magnitude, the inflation episode was largely aseismic